Biorretenção: tecnologia alternativa para manejo de águas pluviais urbanas aplicada a João Pessoa, PB - Azevedo, Flávio Souza (2019)
Green Infrastructure (GI) differs from conventional approaches to open space planning in that it considers conservation values and actions in conjunction with land use development, as well as management and planning of existing infrastructure. With 54% of the world's current population living in urban areas, the consequences of urbanization on urban stormwater drainage are mitigated by Best Management Practices (BMP) and Low Impact Development (LID’s). Considering the complexity of stormwater management, the present work has as its central proposal to investigate what are the local parameters that influence the design and water potential of a bioretention structure as an alternative to current urban drainage practices. Such a device is known as Stormwater Planter or Street Side Rain Garden. The application of the Richards equation to simulate flow in variable depth soil profiles was modeled with the HYDRUS-1D software. Local soil analysis allowed to obtain the specific hydraulic properties for the study site and thus allow the construction of project hydrographs by the NRCS/SCS method for the pre-development and post-development scenarios. The dimensioning of a bioretention system was verified with three different methods: the BIRENICE method, the LID Hydrologic Analysis method and the Hydrogram method. Based on the results obtained in this research, the dimensioning of the bioretention with the LID Hydrologic Analysis method presented the highest volumes. The variation of the return time and the duration of the project storm was investigated and demonstrated that, for times of duration of the order of 60 minutes, the variation in the storage volume is not significant, even when the return time varied from five to 20 years. With the modeling of the hydrological process with HYDRUS-1D, it was proven that the prediction of a 0.20 m high retention layer in the analyzed profiles positively alters the hydrological response of the system, by providing lower flow volumes and maximizing the infiltration of the water profile beyond the duration of the storm. The applicability of the bioretention system was considered with the presentation of a project proposal for the implementation of Stormwater planter in a parking lot at the Federal University of Paraíba (UFPB). The area system obtained was 4.08% of the total area, and the area of existing grassy beds corresponds to 23% of the total area, that is, its implementation is fully viable